Kombinasi Simple Additive Weighted dan Rank Order Centroid Dalam Pemilihan Vendor Catering - Tri Widodo (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
The selection of catering vendors is a crucial stage in planning an event that requires serious attention. The vendor's experience and specialization in serving the desired type of dish is a determining factor, while the ability to tailor the menu to specific needs is a plus. The combination of SAW and ROC can provide a higher level of accuracy in ranking alternatives. SAW provides a simple approach to assigning weight to criteria, while ROC brings the centroid concept to reduce the impact of extreme values. The combination of these two methods can provide more consistent and accurate results. The ranking results of catering vendors using SAW and ROC get the results of rank 1 with a value of 0.8198 for Surya Catering vendors, rank 2 with a value of 0.7972 for Dzaky Catering vendors, rank 3 with a value of 0.7971 for Ratu Catering vendors.